GAY REPRESENTATION IN BECKY ALBERTALLI'S SIMON VS THE HOMO SAPIENS AGENDA - Irvan Gading; Linusia Marsih (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2019)
This study aims to reveal gay habitus in Becky Albertalli's Simon VS The Homo Sapiens Agenda. This study is descriptive qualitative which applies both intrinsic and extrinsic approaches. The intrinsic approach is applied due to the fact that the study deals with the characterization of the main character in the novel. Moreover, the sociological approach is applied because the study is primarily concerned with a social phenomenon reflected inÂ literary work as the novel portrays the representation of gay habitus reflected in the attitude and behaviours of one of the main characters in the novel. In revealing the gay habitus reflected in the novel, Bourdieu's theory of habitus is applied. The discussion is focused on the Simon's habitation as a gay and the factors that contribute to the formation of Simon's habitus as a gay. The result of the study shows that Simon develops gay habitus. The representations of his gay habitus include are having no attraction to the opposite sex, adoring the same sex, obsessing and fantasizing about the same sex, feeling jealous and cynical to the suspected competitors, and falling in love with the same sex. There are two factors that support the development of Simon's gay habitus i.e. primary and secondary socialization.